Naturally occurring chemicals against Alzheimer's disease - Belwal, Tarun; Nabavi, Seyed Mohammad; Nabavi, Seyed Fazel; Dehpour, Ahmad Reza; Shirooie, Samira (Academic Press, an imprint of Elsevier, 2021)
"Provides information on phytochemistry, pharmacology, toxicology, clinical trials, and advancement in formulations specific to Alzheimer's Disease in a single source Explores natural compounds, which can be more affordable to the majority of Alzheimer's Disease patients, who will increasingly be in developing countries Covers a wide array of specific chemical compounds"--